INCLUSION OF THE TOPIC «THE SIMPLEST FUNCTIONAL EQUATIONS» IN THE MODEL PROGRAMS FOR STUDYING THE SUBJECT «ALGEBRA AND THE BEGINNINGS OF ANALYSIS» - Bokhonova, Tetiana; Bokhonov, Yurii; Matvieieva, Iryna; Tomashchuk, Oleksii; Tykhonova, Viktoriia; Leshchynskii, Oleh; Groza, Valentyna (Physical and Mathematical Education, 2023)
Formulation of the problem. Analysis of the issue of including the topic "The simplest functional equations" in the model curricula for studying the subject "Algebra and the beginnings of analysis" for specialized classes with in-depth study of mathematics. A model curriculum studies the approximate sequence of achieving the expected learning outcomes, the content of the subject or integrated course, and the types of students’ educational activities. The inclusion of this topic aims to start a creative understanding of functional relationships existing in real systems and processes, in particular, ecological, economic, and social ones.Materials and methods. Theoretical method of analysis of methodical and educational literature on the researched issue; comparative analysis to understand different views on the problem; systematization and generalization to create recommendations for the content of the proposed topic, as well as formulating conclusions and integrating the pedagogical experience of authors who teach relevant disciplines in educational institutions of various levels.Results. The possible content of the topic "The simplest functional equations" in the model programs for studying the subject "Algebra and the beginnings of analysis", examples for an explanation by the teacher, and confirmation by students are proposed. For some examples, different approaches to their solution are proposed; convenient tables are provided for students to find partial solutions to some types of functional equations.Conclusions. The authors believe that the topic "The simplest functional equations" will be useful and acceptable for studying within the scope of the subject "Algebra and the beginnings of analysis" by students of specialized classes with an in-depth study of mathematics. Within the eleven-year school education, of course, it was impossible to find time to study this topic due to the saturation and density of the material necessary for study. But in the twelve-year New Ukrainian School, marked by a deeper differentiation of specialized education, the topic "The simplest functional equations" can strengthen the fundamentality of mathematical education in classes with in-depth study of mathematics, computer science, etc. Further research in this direction may concern the method of solving the simplest recurrent equations.
Keywords: function of one variable; functional equations; general solution of a functional equation; partial solution of a functional equation; injectivity of a function